FRAMING HAMAS: A COMPARATIVE DISCOURSE ANALYSIS OF WESTERN AND MIDDLE EASTERN MEDIA - Henarni, Nabila Humairo; Surwandono, Surwandono (al-Balagh : Jurnal Dakwah dan Komunikasi, 2024)
After the 9/11 attacks, Western society, especially the United States, began to consider Islam as a religion that gave birth to terrorist organizations. Many media also brand organizations related to the Islamic religion as terrorists, including Hamas. In order to emphasize the intricate relationships between media, geopolitics, and the formation of public opinion, this research seeks to analyze potential biases and contrasting narratives between Western and Middle Eastern opinions on Hamas. In order to examine depictions of Hamas as a "hero," "terrorist," "cruel," and exhibiting "humane" treatment towards civilians and hostages, this study used NVivo 12 Plus to analyze 150 news stories, 75 of which came from Middle Eastern (Al-Jazeera, Al-Arabiya, Asharq Al-Awsat) and 75 from Western (BBC, CNN, The Guardian) media sources. The findings indicate that Western media typically adopts a more solemn narratives, emphasizing Hamas-related conflict and violence. However, the narrative from Middle Eastern media emphasizing Hamas-related themes of resistance and heroism. This research can assist journalists and media organizations recognize potential biases and differing narratives in their coverage of Hamas and related subjects.